Spatiotemporal dynamics of woody species diversity and community structure in the forests of Zegie Peninsula and monasteries of Lake Tana, Ethiopia: Implications for biodiversity conservation - Abebe Worku Amberbir; Getahun Yemata Lule; Amare Bitew Mekonnen (Journal for Nature Conservation, 2026)

Evaluating the performance of selected CMIP6 GCMs for simulations of historical temperature over Ethiopia - Alehegn Belay Tagele; Temesgen Gashaw Tarkegn; Pieter R. van Oel; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Othoo Calvince Ouko; Daniel Berhanu; Amare Haileslassie; Abeyou W. Worqlul; Amare Bantider; et al. (Theoretical and Applied Climatology, 2026)
This study evaluates the performance of seven Global Climate Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and their Ensemble mean in reproducing historical maximum (Tmax) and minimum (Tmin) temperatures across five agro-ecological zones (AEZs) of Ethiopia during 1995–2014. The assessment covers daily to annual time scales using observational and GCM datasets. Model performance was evaluated using Percent Bias (PBIAS), Root Mean Square Error (RMSE), and correlation coefficient (r), while the Comprehensive Rating Index (CRI) was applied for ranking. Results show substantial spatial and temporal variability in model performance. For Tmax, the Ensemble mean and EC-Earth3-veg performed best at the daily scale, while EC-Earth3-veg, MPI-ESM1-2-LR and BCC-CSM2-MR excelled at the monthly scale across most AEZs. Seasonally, top-performing models included Ensemble mean, MPI-ESM1-2-LR and MRI-ESM2-0 during Bega (October-January), EC-Earth3-veg, CNRM-CM6-1 and Ensemble mean during Belg (February-May) and CNRM-CM6-1 and MPI-ESM1-2-LR during Kiremt (June-September). For Tmin, CNRM-CM6-1, BCC-CSM2-MR and Ensemble mean ranked highest at both daily and monthly scales in most AEZs. At the annual scale, MRI-ESM2-0, Ensemble mean, MPI-ESM1-2-LR and CNRM-CM6-1 excel for Tmax, while EC-Earth3-veg, BCC-CSM2-MR and Ensemble mean lead for Tmin across most AEZs. MIROC6 consistently exhibited the weakest performance for both Tmax and Tmin across most AEZs and time periods. Thus, the Ensemble mean of all evaluated models does not consistently rank among the top three performers across all AEZs and time scales. The identified best-performing CMIP6 models provide valuable tools for assessing climate change impacts and developing region-and time-specific adaptation strategies in Ethiopia. Given the variability in GCM performance across AEZs and time scales, national or large-scale studies would benefit from using the Ensemble mean derived from the best-performing models. This study provides crucial insights into the strengths and weaknesses of different GCMs, supporting evidence-based decision-making and enhancing efforts to build climate resilience and adaptation strategies in the region.

Correction: Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in Lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Advances in solar energy technologies: A comprehensive review of photovoltaic, thermal, and hybrid systems for sustainable energy solutions - Solomon Tibebu Gebreabe; Daniel Bogale; Arkbom Hailu; Abebe Worku (Next Research, 2026)

Response surface optimization of turbidity removal from highly turbid surface water using orange peel powder as a sustainable coagulant - Solomon Tibebu Gebreabe; Abebe Worku; Mikiyas Abewaa Gnaro; Estifanos Kassahun; Tigabu Haddis Ale; Takele Sime; Bimrew Bizualem; Shiferaw Ayalneh; Andualem Arka Ammona (Next Research, 2025)

Assessment of deep-water wells drawdown: A case study of legedadi deep well field phase I, Addis Ababa, Ethiopia - Abenezer Zelalem; Abebe Worku; Solomon Tibebu (Groundwater for Sustainable Development, 2025)

Improving climate information through projecting climate change and variability in the Upper Awash Subbasin, Ethiopia - Abebe Bezu Bedada; Gudina Legese Feyisa; Asfaw Kebede; Majaliwa Mwanjalolo; Gabiri Geofery; Mitiku Adisu Worku; Elias Abdi (Meteorology and Atmospheric Physics, 2025)

Determination of tolerable soil loss limit using quantitative biophysical model: a case study in Andit Tid watershed, central highland of Ethiopia - Tilahun Getachew Abebe; Tesfaye Mebrate Lemma; Tesfa Worku Meshesha; Estifanos Lemma; Fikrey Tesfay (Environmental Monitoring and Assessment, 2025)

Prevalence of Intestinal Parasitic Infections and Associated Factors Among Food Handlers in East Africa: A Systematic Review and Meta-analysis - Agenagnew Ashagre; Tadesse Misganaw; Wagaw Abebe; Zelalem Dejazmach; Gashaw Azanaw Amare; Yenesew Mihret Wondmagegn; Kassahun Misgana Worku; Adane Adugna; Hassen Ahmed; Solomon Gedifie; Getinet Kumie; Marye Nigatie; et al. (Acta Parasitologica, 2025)

Performances of reanalysis products in representing the temperature climatology of Ethiopia - Tazebew Abera Tadesse; Temesgen Gashaw Tarkegn; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Abeyou W. Worqlul; Pieter R. van Oel; Yihun T. Dile; Abebe D. Chukalla; Amare Haileslassie; Endeg Aniley; et al. (Theoretical and Applied Climatology, 2025)

Grain and flour physical and functional characteristics of Tef [Eragrostis tef (Zucc) Trotter] varieties of Ethiopia - Tamrat Kore Menjaye; Kebebew Assefa; Oli Legese; Muhaba Seifu; Worku Kebede; Workineh Abebe; Lamsgen Yegrem; Deribe Mengistu; Semhal Marsha; Teshome Mesfin; Solomon Chanyalew (Journal of Cereal Science, 2024)

Seroprevalence and associated risk factors of equine herpesvirus type-1/-4 in selected districts of Northwest Amhara, Ethiopia - Anmut Worku; Wassie Molla; Ambaye Kenubih; Daniel Gizaw; Ayelech Muluneh; Bemrew Admassu; Mebrat Ejo; Gashaw Getaneh Dagnaw; Abebe Belete Bitew; Tewodros Fentahun; Kalkidan Getnet; Haileyesus Dejene; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Correction to: Investigation of Pumpkin Seed as a Potential Coagulant for Drinking Water Treatment - Yohannes Gatew; Abebe Worku (Water Conservation Science and Engineering, 2023)

Investigation of Pumpkin Seed as a Potential Coagulant for Drinking Water Treatment - Yohannes Gatew; Abebe Worku (Water Conservation Science and Engineering, 2023)

Review of herbal medications with the potential to cause bleeding: dental implications, and risk prediction and prevention avenues - Worku Abebe (EPMA Journal, 2019)

Constructed wetlands for phytoremediation of industrial wastewater in Addis Ababa, Ethiopia - Abebe Worku; Nurelegne Tefera; Helmut Kloos; Solomon Benor (Nanotechnology for Environmental Engineering, 2018)

Status of stem cells in diabetic nephropathy: predictive and preventive potentials - Babak Baban; Jun Yao Liu; Samuel Payne; Worku Abebe; Jack C. Yu; Mahmood S. Mozaffari (EPMA Journal, 2016)

The impact of traditional coffee processing on river water quality in Ethiopia and the urgency of adopting sound environmental practices - Abebe Beyene; Yared Kassahun; Taffere Addis; Fassil Assefa; Aklilu Amsalu; Worku Legesse; Helmut Kloos; Ludwig Triest (Environmental Monitoring and Assessment, 2012)

Endothelial dysfunction in diabetes: potential application of circulating markers as advanced diagnostic and prognostic tools - Worku Abebe; Mahmood Mozaffari (EPMA Journal, 2010)

Urban impact on ecological integrity of nearby rivers in developing countries: the Borkena River in highland Ethiopia - Abebe Beyene; Worku Legesse; Ludwig Triest; Helmut Kloos (Environmental Monitoring and Assessment, 2009)